MICROBIOLOGICAL ACTIVITY OF LIQUID PHARMACOPOEIA FORMS OF APPLE PECTIN WHEN DEVELOPING RINSE FOR ORAL CAVITY IN RESEARCH IN VITRO - Haioshko, E.B. (World of Medicine and Biology, 2016)
Innovative technologies for improving conditions of wounds healing when extracting teeth are based on the modern approach of curing patients with extracted teeth. Upon developing innovations, it was taken into consideration three types of groups of impact factors with wounds healing: I group – general; II group – local; III group – curing technologies of postopeartional wounds. Their integration occurred due to the reasonable actions and means based on pectin. Pectin was used both locally for shape generating the stomatological bandage and for the intake use as well as the hygienic-prophylactic mean. It was also reasonable to develop the liquid water medicine based on pectin as the rinse for oral cavity without antibiotics that prevented from the creation of microbial colonies and plankton sedimentation.